Significance of Iqbal’s Wisdom Poetry - Umar, Muhammad Suheyl (Intellectual Discourse, 2013)
The distinguishing feature of Iqbal’s poetry is his "conscious concerns" about issues vital to the Ummah. These concerns also provide the key to understand the psycho-dynamics of Iqbal’s mind and help us to appreciate the reasons for which his poetry has become meaningful for the Ummah. Iqbal’s poetry has to be considered as "contemplative or higher poetry" in that the response is born of his intellect. Iqbal is a poet of "intellectual conception" and "intuition expression" wherein the inner meaning dominates totally over the form. The "vital operation" of which Iqbal’s poetry is a manifestation is an intellectual conception born of the poet’s wisdom.